Perceraian dalam Perspektif Hadits Riwayat Abu Dawud dan Pasal 39 Ayat (2) UU No. 1 Tahun 1974 - Erni Erni; Tajul Arifin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The practice of divorce without going through a formal court process, commonly referred to as informal or unregistered divorce, remains prevalent in Indonesian society despite clear regulations outlined in Law Number 1 of 1974 on Marriage. This paper aims to examine the legal dimensions of such practices and explore the social and psychological impacts, particularly on children. Findings indicate that divorces conducted outside the legal framework not only violate national laws but also often result in disadvantages for vulnerable parties, especially women and children. In Islamic teachings, while divorce is permissible, it is considered the most detested lawful act by Allah and should only be pursued after all efforts at reconciliation have failed. National legal provisions echo this perspective by emphasizing mediation and the principle of justice as primary steps in resolving marital disputes. This alignment reflects a harmony between religious norms and state law. Therefore, public awareness of proper legal procedures for divorce needs to be enhanced to protect individual rights and preserve family stability. Strengthening legal education and premarital counseling are effective preventive strategies in this regard.